The Bolivian fauna of the genus Anastrepha Schiner (Diptera: Tephritidae) - Ramos, Elizabeth Quisberth; Norrbom, Allen L.; Marinoni, Luciane; Sutton, Bruce D.; Steck, Gary J.; Sánchez, Juan José Lagrava (Zootaxa, 2021)
The general aim of this study is to contribute to and summarize knowledge of the Bolivian fauna of the genus Anastrepha Schiner (Tephritidae) which includes species of both ecological and economic importance. In addition to compiling data from the literature, we report the results of fruit fly sampling using McPhail or multilure traps in the Tropic of Cochabamba region and at the private natural reserve of Potrerillo del Guendá in Santa Cruz de la Sierra, as well as records from various other sites based on specimens in museum collections. Fifty-seven named species and three unnamed species of Anastrepha are recorded from Bolivia. Distribution maps for all of these species are provided. Numerous new department records are reported as well as the first records for Bolivia of A. castanea Norrbom, A. dissimilis Stone, A. elegans Blanchard, A. haywardi Blanchard, A. macrura Hendel, A. montei Lima, A. punctata Hendel, and A. rosilloi Blanchard. Pacouria boliviensis (Markgr.) A. Chev. (Apocynaceae) is reported as a host plant of A. woodleyi Norrbom & Korytkowski, and Myrciaria floribunda (H. West ex Willd.) Berg (Myrtaceae) and Pouteria glomerata (Miq.) Radlk. (Sapotaceae) as host plants of A. fraterculus (Wiedemann). This distribution and host information will be useful to monitor and manage species that damage fruit crops in Bolivia.